A Synopsis of Tax Accounting and Livestock in Australia: Insights from the Wade Case - Fullarton, Lex; Pinto, Dale (2024)
This paper is a synopsis of the book Tax Accounting and Livestock in Australia: Insights from the Wade Case. The book is a detailed examination of the taxation implications of the disposal of animals held in a business of primary production in conjunction with the sale of a farm or pastoral lease. In the pastoral and farming industries, valuable stud animals are not normally sold as trading stock but, as a consequence of a natural or family disaster, they may need to be disposed of against the will of the owners. In Australia, the Australian Taxation Office (ATO)’s view is that the revenue from the sale of all animals held as part of a primary production business is income according to ordinary concepts, regardless of the function of those animals in the business or the reasons for sale, and the receipts are taxed as ordinary income. That view deprives owners of a raft of tax concessions granted to other business owners on the sale of their businesses. The authors consider this situation to be grossly unfair to pastoralists, farmers and graziers if they are forced to sell their breeding stock as a result of a natural disaster or along with the sale of their business on their retirement from the industry. The book looks at how the ATO’s view was established and why it came into being. It looks at the basis on which the ATO formed its view and examines the litigation which the ATO uses to support its opinion – Federal Commissioner of Taxation v Wade (‘Wade Case’). It then examines the background of the Wade Case in detail, and the court documents presented in the preceding trial and administrative reviews